Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Hà Thị Hương Giang

1/2* x+2/3=9/2

1/2*x-1/3=2/3

1/4+3/4:x=3

giúp mình với mình đang cần gấp

 

1/2* x+2/3=9/2

1/2 * x = 9/2 - 2/3 

1/2 * x= 23/6

x= 23/6 : 1/2

x= 23/6 x 2= 23/3

___

1/2*x-1/3=2/3

1/2*x = 2/3 + 1/3

1/2 * x= 1

x= 1: 1/2 

x= 2

____

1/4+3/4:x=3

3/4 : x = 3 - 1/4

3/4 : x= 11/4

x= 11/4 : 3/4

x= 11/3

\(\dfrac{1}{2}\)\(\times\)\(x\) + \(\dfrac{2}{3}\) = \(\dfrac{9}{2}\)

\(\dfrac{1}{2}\)\(\times\)\(x\)        = \(\dfrac{9}{2}\) - \(\dfrac{2}{3}\)

\(\dfrac{1}{2}\)\(\times\)\(x\)       = \(\dfrac{23}{6}\)

      \(x\)       = \(\dfrac{23}{6}\):\(\dfrac{1}{2}\)

      \(x\)      = \(\dfrac{23}{3}\) 

\(\dfrac{1}{2}\)\(\times\)\(x\) - \(\dfrac{1}{3}\) = \(\dfrac{2}{3}\) 

\(\dfrac{1}{2}\)\(\times\)\(x\)       = \(\dfrac{2}{3}\) + \(\dfrac{1}{3}\)

\(\dfrac{1}{2}\times\)\(x\)      =  1

     \(x\)       = 1 : \(\dfrac{1}{2}\)

   \(x\)         = 2

\(\dfrac{1}{4}\) + \(\dfrac{3}{4}\)\(x\) = 3

          \(\dfrac{3}{4}\)\(x\) = 3 - \(\dfrac{1}{4}\) 

          \(\dfrac{3}{4}\):\(x\) = \(\dfrac{11}{4}\)

              \(x\) = \(\dfrac{3}{4}\)\(\dfrac{11}{4}\)

             \(x\) = \(\dfrac{3}{11}\)

     

Nguyễn Hoàng Ngọc Linh
8 tháng 7 2023 lúc 8:51

` @ L I N H `

1/2* x+2/3=9/2

1/2 * x = 9/2 - 2/3 

1/2 * x= 23/6

x= 23/6 : 1/2

x= 23/6 x 2= 23/3

___

1/2*x-1/3=2/3

1/2*x = 2/3 + 1/3

1/2 * x= 1

x= 1: 1/2 

x= 2

____

1/4+3/4:x=3

3/4 : x = 3 - 1/4

3/4 : x= 11/4

x= 11/4 : 3/4

x= 11/3


Các câu hỏi tương tự
Lê Quang Huy
Xem chi tiết
Trần Mai Khanh
Xem chi tiết
Ky Nguyen
Xem chi tiết
nghiêm minh châu
Xem chi tiết
Nguyen Phuong Thao
Xem chi tiết
Lê Quang Huy
Xem chi tiết
Hoàng Ngọc Trúc Quỳnh
Xem chi tiết
Nguyễn Hải Vân
Xem chi tiết
Bùi Hà My
Xem chi tiết